An abrupt weakening of the subpolar gyre as trigger of Little Ice Age-type episodes - Moreno-Chamarro, Eduardo; Zanchettin, Davide; Lohmann, Katja; Jungclaus, Johann H. (Climate Dynamics, 2017)
We investigate the mechanism of a decadal-scale weakening shift in the strength of the subpolar gyre (SPG) that is found in one among three last millennium simulations with a state-of-the-art Earth system model. The SPG shift triggers multicentennial anomalies in the North Atlantic climate driven by long-lasting internal feedbacks relating anomalous oceanic and atmospheric circulation, sea ice extent, and upper-ocean salinity in the Labrador Sea. Yet changes throughout or after the shift are not associated with a persistent weakening of the Atlantic Meridional Overturning Circulation or shifts in the North Atlantic Oscillation. The anomalous climate state of the North Atlantic simulated after the shift agrees well with climate reconstructions from within the area, which describe a transition between a stronger and weaker SPG during the relatively warm medieval climate and the cold Little Ice Age respectively. However, model and data differ in the timing of the onset. The simulated SPG shift is caused by a rapid increase in the freshwater export from the Arctic and associated freshening in the upper Labrador Sea. Such freshwater anomaly relates to prominent thickening of the Arctic sea ice, following the cluster of relatively small-magnitude volcanic eruptions by 1600 CE. Sensitivity experiments without volcanic forcing can nonetheless produce similar abrupt events; a necessary causal link between the volcanic cluster and the SPG shift can therefore be excluded. Instead, preconditioning by internal variability explains discrepancies in the timing between the simulated SPG shift and the reconstructed estimates for the Little Ice Age onset.